Integration of concepts about lean construction, sustainability and life cycle of buildings: a literature review - Besser Freitag, Alberto Eduardo (2017)
The purpose of this study was the development of a theoretical framework integrating concepts of lean construction, sustainability and the life cycle of buildings. It was prepared using a systematic review of the literature through the Prisma method. Findings show that there is scarce scientific literature about lean construction contributions to activities related to the consumption phase of the life cycle of a building. Project and construction activities presented the highest number of lean construction contributions in the production phase. Research limitations are terms used in the search sentences and the choice of surveyed databases. The study contributes with knowledge that can be used by companies to adopt lean construction. It is also useful for researchers who can explore several research lines. The originality of this research is to view in a same table the interrelationship of concepts about lean construction, sustainability and the life cycle of buildings.